Analisis Faktor Internal Nilai - Nilai Perusahaan Tembakau yang Terdaftar di Bei Periode 2019-2023 - Lailatus Sa’adah; Adinda Tiara Choirunnisa; Gilang Noratama; Rio Eka Pebrianto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to analyze the impact of Return on Equity (ROE), Return on Assets (ROA), and Earnings Per Share (EPS) on firm value in the tobacco sector companies listed on the Indonesia Stock Exchange (IDX). The results show that a high ROE, as seen in HMSP, reflects efficient equity management and positively contributes to increased firm value, while low ROE in GGRM and ITIC indicates inefficiency. ROA analysis reveals that all four issuers have very high average ROA, indicating efficiency in utilizing assets to generate profits. Regarding EPS, the increase in ITIC and WIIM reflects improved financial performance, whereas the decline in EPS at GGRM and HMSP may reduce investor attractiveness. Overall, the study concludes that ROE, ROA, and EPS are important indicators influencing firm value, although they should be considered along with other external factors for a more comprehensive understanding.